CD19-CAR T-cell therapy induces deep tissue depletion of B cells - Tur, Carlo; Eckstein, Markus; Velden, Joachim; Rauber, Simon; Bergmann, Christina; Auth, Janina; Bucci, Laura; Corte, Giulia; Hagen, Melanie; Wirsching, Andreas; Grieshaber Bouyer, Ricardo; Reis, Petra; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives CD19-targeting chimeric antigen receptor (CAR) T-cell therapy can induce long-term drug-free remission in patients with autoimmune diseases (AIDs). The efficacy of CD19-CAR T-cell therapy is presumably based on deep tissue depletion of B cells; however, such effect has not been proven in humans in vivo. Methods Sequential ultrasound-guided inguinal lymph node biopsies were performed at baseline and after CD19-CAR T-cell therapy in patients with AIDs. Results were compared with lymph node biopsies from rituximab (RTX)-treated AID patients with absence of peripheral B cells. Conventional and immunohistochemistry staining were performed on lymph node tissue to assess architecture as well the number of B cells, follicular dendritic cells (FDCs), plasma cells, T cells and macrophages. Results Sequential lymph node biopsies were analysed from five patients with AID before and after CD19-CAR T-cell therapy and from five patients with AID after RTX treatment. In addition, non-lymphoid organ biopsies (colon, kidney and gallbladder) from three additional patients with AID after CD19-CAR T-cell therapy were analysed. CD19+ and CD20+ B cells were completely depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX treatment. Plasma cells, T cells and macrophages in the lymph nodes remained unchanged. Follicular structures were disrupted and FDCs were depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX. Non-lymphoid organs were completely depleted of B cells. Discussion This study demonstrates complete B-cell depletion in secondary lymphoid tissues of patients with AIDs following CD19-CAR T-cell therapy combined with standard lymphodepleting therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Autoimmune Diseases; B-Lymphocytes; Rituximab; Ultrasonography

Donor-Derived Cell-Free DNA as a Companion Biomarker for AMR Treatment With Daratumumab: Case Series - Osmanodja, Bilgin; Akifova, Aylin; Budde, Klemens; Oellerich, Michael; Beck, Julia; Bornemann-Kolatzki, Kirsten; Schütz, Ekkehard; Velden, Joachim; Lehmann, Claudia; Krüger, Bastian Malte; Bachmann, Anette; Kowald, Jan (Transplant International, 2024)
Antibody-mediated rejection (AMR) is among the most frequent causes for graft loss after kidney transplantation. While there are no approved therapies, several case reports with daratumumab and the very recent phase 2 trial of felzartamab in AMR have indicated the potential efficacy of therapeutic interventions targeting CD38. Donor-derived cell-free DNA (dd-cfDNA) is an emerging biomarker with injury-specific release and a short half-life, which could facilitate early diagnosis of AMR and monitoring of treatment response. We describe two cases of patients with chronic active AMR, who were treated with monthly daratumumab infusions, and in whom donor-derived cell-free DNA (dd-cfDNA) was measured longitudinally to monitor treatment response. In both patients, daratumumab treatment led to stabilization of kidney function parameters, a strong decline of dd-cfDNA below the previously established threshold for rejection, and partial or complete histologic resolution of AMR activity. Our case series suggests that dd-cfDNA may be a useful companion biomarker for longitudinal monitoring of anti-CD38 treatment in patients with AMR.
CRIS-Team Scopus Importer:2024-08-30
Keywords: antibody-mediated rejection; biomarker; daratumumab; donor-derived cell-free DNA; kidney transplantation

Nephropathologie infektiöser Erkrankungen - Büttner-Herold, Maike; Amann, Kerstin Ute; Velden, Joachim (Die Pathologie, 2024)
Infections can affect the kidney via different pathways. Urinary tract infections can directly involve the renal tissue by spreading along pre-existing canalicular structures. Such an ascending infection can manifest as a highly active and purulent or even abscessing interstitial nephritis or as a chronic-fibrosing process in recurrent pyelonephritis. Viral infections can also use the canalicular route as in polyomavirus nephropathy or spread via the blood stream in a hematogenous manner as in the case of cytomegalovirus or hantavirus infections. Likewise, bacterial infections can reach the kidney via the blood in the case of systemic infection. Another large group of nephropathies taking place as a sequel of infections includes infection-related glomerulonephritides (IRGN), which are mediated by a series of immunological mechanisms. These IRGN can be subdivided according to their temporal association with the infectious process, occurring either after the infection has healed (postinfectious) or accompanying the ongoing infectious process (parainfectious). The latter, in particular, is of increasing importance in the daily practice of nephropathologists, especially in older patients. A number of other glomerulonephritis forms, i.e., membranous or membranoproliferative forms, can occur as a consequence of infection. In addition, infections can trigger nephropathies, such as thrombotic microangiopathy. The present article gives an overview of morphologic changes in renal parenchyma that take place as a consequence of infectious processes, with particular focus on IRGN.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Immune complex; Infection-related glomerulonephritis; Path of infection; Pathogen spectrum; Urinary tract infection